The Tourism Function of Mountain Areas - Kurek, Włodzimierz (Turyzm/Tourism, 2005)
The article presents both current and prospective tourism development in mountain areas. The author pays particular attention to the spatial concentration of tourism, its seasonality, transport problems and activities (hiking, skiing and agro-tourism) as well as to ideas for harmonious tourism development. Sustainable development being seen as the most desirable option.